The nexus between tourism and immigration : a study of travel patterns of Chinese New Zealanders : a 52.787 thesis presented in partial fulfillment of the requirements of the degree of Master of Business Study at Massey University - Feng, Kathy L (Massey University, 1999)
With the worldwide increase in migration and tourism, the issue of ethnicity has become a major discriminating factor in population movements around the world. Therefore, there is a growing research interest in the area of ethnic tourism. This study examines the travel patterns and travel habits of the Chinese population in New Zealand, particularly, those of the recent immigrants to the country with a focus on the impact of family ties and kinship in motivating travel for family reunion. It also examines the impact of family reunion, Visiting Friends and Relatives travel and other factors in shaping the travel patterns of Chinese immigrants in New Zealand by comparing the Chinese New Zealanders' travel patterns with the travel patterns of New Zealanders and the travel patterns of the Chinese from China. This study provides one example of ethnic tourism in gaining a better understanding of the nexus between tourism and immigration. This may also form a basis for comparative studies between different ethnic groups in terms of their patterns of outbound travel. The study also develops a number of themes which require further research and development to establish the extent to which such patterns are indicative of global processes shaping the travel habits of immigrant groups. This study commences with a review of the limited literature on the interface of tourism, migration and globalization as a basis for establishing the conceptual framework for the study. This is followed by a detailed study of the demographic profile of Chinese population in New Zealand to establish the context of Chinese immigration. A questionnaire survey was conducted in June 1999 to examine the tourism-migration nexus and the results were evaluated using correspondence analysis and other quantitative statistical methods to establish the dimensions and extent of ethnic outbound travel within New Zealand. Research that could further substantiate the results is also suggested in the conclusion.
Keywords: New Zealand tourism; Chinese tourists; Tourism and immigration